Thrombosis Prevention with Botulinum Toxin A after Traumatic Crush Injury in a Rat Model - Hassanpour, Seyed Esmail; Tarahomi, Mohammadreza; Daryani, Amir (Journal of Reconstructive Microsurgery, 2018)
Background Revascularized digits may fail because of vessel thrombosis. The current study aimed to develop a standard model for crush injury in the rat femoral artery to evaluate the antithrombotic effect of perivascular botulinum toxin A (BTX-A) injection.Methods We explored bilateral femoral arteries of 10 rats using a microscopic technique. The crush injury was reproduced using a bulldog clamp. One randomly chosen leg of each rat was injected with BTX-A. The other side received normal saline as its own control. After 24 hours, the femoral arteries were ligated distal to the trauma site and were divided between the traumatized and ligated sites.Results All arteries injected with BTX-A had pulsatile bleeding without thrombosis. Arteries injected with normal saline had thrombosis without bleeding, except for one with oozing. The results showed the efficacy of BTX-A and its potential use in microvascular trauma (p < 0.001).Conclusion The use of BTX-A preoperatively in the emergency department may help reduce traumatic stress and subsequent thrombosis and improve trauma management results. Complementary studies are needed to assess the ability of BTX-A to reduce thrombosis and vasospasm and improve survival of traumatized digits.
Keywords: botulinum toxin A; thrombosis; microvascular